Does Strategic Management Accounting, Local Wisdom Influence Village-Owned Enterprises Performance? An Applied Study in Indonesia - Marlina, Evi; Rodiah, Siti; Mualfah, Desti; Audina, Sandra (International Review of Management and Marketing, 2025)
The high role of village-owned enterprises (VOEs) in encouraging the improvement of the rural economy, so the demand to improve the performance of VOEs is a challenge for VOEs managers. This is due to limited resources and high levels of competition. This paper aims to test several factors that can encourage the improvement of the performance of VOEs, namely strategic management accounting (SMA), this is related to ensure the effectiveness and efficiency of organizational management. In addition, because the existence of VOEs in rural areas is considered local wisdom so that the existence of VOEs receives support from the local community. This study uses SEM-PLS to test the influence of SMA and local wisdom on the performance of VOEs. By using primary data obtained by distributing questionnaires to 276 VOEs spread across the province of Riau, Indonesia. The findings of the study show that SMA and local wisdom have a significant effect on the performance of VOEs.